Anies-Cak Imin Change Coalition in Detik.com and Suara.com Framing - Annisa, Firly; Suryawati, Indah (representamen, 2024)
The declaration of Anies-Cak Imin (AMIN) on September 2, 2023, was officially held at the Majapahit Hotel, Surabaya, promoting a coalition of change with the intention of realizing a more advanced and just Indonesia. During the declaration, the AMIN pair took turns delivering their political speeches. Anies stated that the coalition of change was formed with good intentions and noble aspirations, which serve as a moral responsibility for the republic. Cak Imin also expressed his readiness to participate in the coalition of change, which aims to move towards a better direction. The objective of this research is to examine how the news framing on the national media outlets Detik.com and Suara.com relates to AMIN within the coalition of change. It will analyze the political messages conveyed through the political news in the selected media. This analysis uses the framing method of Zhongdang Pan and Gerald M. Kosicki, focusing on how mass media shapes public perception of an issue or policy and employing a qualitative approach to gain a deeper understanding of human and social issues. Pan and Kosicki's analysis consists of four structures: syntactic, script, thematic, and rhetorical. Each of these structures provides a detailed analysis of the focus of the media being studied. The data collection techniques in this research use primary data from online news and secondary data from books and journals related to framing. The results of this research reveal differences in the coverage between the two national media, Detik.com and Suara.com. It shows that each news outlet presents a different perspective on the Anies-Cak Imin coalition of change, with each applying different framing techniques based on the structures outlined by Pan and Kosicki. The analysis concludes that each media outlet frames the coalition of change by focusing on different issues, which becomes the unique appeal of the news framing by Detik.com and Suara.com. Keywords: Coalition of change, Framing, Zhongdan Pan and Gerald M.Kosicki, Detik.com, Suara.com.